Digitalization, agility, and customer value in tourism - Hadjielias, Elias; Christofi, Michael; Christou, Prokopis A.; Drotarova, Maria Hadjielia (My University, 2022)
The present study investigates the way strategic agility underpins digitalization and customer value outcomes in tourism. Drawing on an abductive logic, in-depth interviews were carried out with 34 managers of tourism organizations in Cyprus. The findings highlight the role of three interrelated agility capabilities - customer, partnering, and operational - in enabling tourism organizations to leverage digital technologies to produce and/or deliver customer value, while responding to tensions inherent within each agility dimension. Customer agility enables tourism organizations to draw on digital technologies to interact with customers in order to source ideas, test services, and attract new customers. Partnering agility allows tourism providers to use digital technologies to interact with partners and thereby create and/or deliver new value. Operational agility leverages digital technologies to achieve effectiveness and speed in value creation and delivery. Drawing on the tourism context, the present study provides context-based theorization of the way strategic agility enables tourism organizations to leverage digital technologies to create and/or deliver customer value in tourism.
Keywords: Strategic agility; Tourism organizations; Value creation; Value delivery; Digitalization